Isolated during adolescence: long-term impact on social behavior, pain sensitivity, and the oxytocin system in male and female rats - Graf, Akseli; Hansson, Anita C.; Spanagel, Rainer (Biology of sex differences, 2024)
Adolescent social isolation (ASI) has profound long-term effects on behavioral and neural development. Despite this, the specific long-term impact of ASI during different adolescent stages and across sexes remain underexplored.
Gesehen am 27.03.2025